Developing a performance index model for a finance shared service centre. - Chua, Kim Heng. (2011)
The deployment of Shared Service Centres (SSCs) by international firms has been rather widespread in recent years, especially across major industries. Rather than outsourcing their common functions to external parties, firms prefer to centralize these processes to maintain a certain level of efficiency and performance. To date, many academic papers have sought to discuss and analyze the performance measurement of the SSCs. This is crucial in helping firms assess their operational effectiveness. However, few of such research efforts have performed in-depth analysis on the banking industry.